Ceramide 1-Phosphate Protects Endothelial Colony–Forming Cells From Apoptosis and Increases Vasculogenesis In Vitro and In Vivo. Issue 10 (October 2019) - Mena, Hebe Agustina; Zubiry, Paula Romina; Dizier, Blandine; Mignon, Virginie; Parborell, Fernanda; Schattner, Mirta; Boisson-Vidal, Catherine; Negrotto, Soledad
Abstract : Objective: Ceramide 1-phosphate (C1P) is a bioactive sphingolipid highly augmented in damaged tissues. Because of its abilities to stimulate migration of murine bone marrow–derived progenitor cells, it has been suggested that C1P might be involved in tissue regeneration. In the present study, we aimed to investigate whether C1P regulates survival and angiogenic activity of human progenitor cells with great therapeutic potential in regenerative medicine such as endothelial colony–orming cells (ECFCs). Approach and Results: C1P protected ECFC from TNFα (tumor necrosis factor-α)-induced and monosodium urate crystal–induced death and acted as a potent chemoattractant factor through the activation of ERK1/2 (extracellular signal-regulated kinases 1 and 2) and AKT pathways. C1P treatment enhanced ECFC adhesion to collagen type I, an effect that was prevented by β1 integrin blockade, and to mature endothelial cells, which was mediated by the E-selectin/CD44 axis. ECFC proliferation and cord-like structure formation were also increased by C1P, as well as vascularization of gel plug implants loaded or not with ECFC. In a murine model of hindlimb ischemia, local administration of C1P alone promoted blood perfusion and reduced necrosis in the ischemic muscle. Additionally, the beneficial effects of ECFC infusion after ischemia were amplified by C1P pretreatment, resulting in a further and significant enhancement of leg reperfusion and muscle repair. Conclusions: Our findings suggest that C1P may have therapeutic relevance in ischemic disorders, improving tissue repair by itself, or priming ECFC angiogenic responses such as chemotaxis, adhesion, proliferation, and tubule formation, which result in a better outcome of ECFC-based therapy. Abstract : Supplemental Digital Content is available in the text.